The dark side of entertainment? How viral entertaining media build an attention base for the far-right politics of The Epoch Times - Peng, Yilang; Yang, Tian; Fang, Kecheng (New media & society, 2025)
To amplify their audience reach, far-right outlets need a calculated and coordinated array of acts to set the stage for audience attention and to build a communication network that spreads their messages. We examined the Facebook newsfeed history of The Epoch Times (N = 117,274 posts from 2013 to 2020), which transitioned from a niche anti-China publication to an influential player in US far-right politics. We found that US partisan issues helped the outlet attract immediate audience engagement, but such content did not invite audience growth and engagement with future content. In contrast, viral entertaining videos, while seemingly benign and mundane, demonstrated superb effects in getting audience responses, accumulating followers, and boosting engagement with subsequent posts. We argue that entertainment media is a crucial component of the extreme politics landscape that directs the flows of political attention, which could exert a “ripple effect” on assembling audience networks.